2022
DOI: 10.1186/s12951-022-01309-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipid based nanoparticles as a novel treatment modality for hepatocellular carcinoma: a comprehensive review on targeting and recent advances

Abstract: Liver cancer is considered one of the deadliest diseases with one of the highest disease burdens worldwide. Among the different types of liver cancer, hepatocellular carcinoma is considered to be the most common type. Multiple conventional approaches are being used in treating hepatocellular carcinoma. Focusing on drug treatment, regular agents in conventional forms fail to achieve the intended clinical outcomes. In order to improve the treatment outcomes, utilizing nanoparticles—specifically lipid based nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 357 publications
(337 reference statements)
0
50
0
Order By: Relevance
“…Another potentially impactful application of LNP technology is modification to exploit stimuli-responsive properties. Internal (e.g., pH, enzyme and redox) and external (e.g., temperature, light, ultrasound and magnetic fields) stimuli have been explored for a variety of nanoparticle platforms [ 80 , 81 , 82 , 83 , 84 ], with Celsion Corporation’s ThermoDox arguably the most well-known example [ 85 , 86 , 87 ]. There are several reports in the literature using internal and external stimuli to afford the release of nucleic acid cargos.…”
Section: Discussionmentioning
confidence: 99%
“…Another potentially impactful application of LNP technology is modification to exploit stimuli-responsive properties. Internal (e.g., pH, enzyme and redox) and external (e.g., temperature, light, ultrasound and magnetic fields) stimuli have been explored for a variety of nanoparticle platforms [ 80 , 81 , 82 , 83 , 84 ], with Celsion Corporation’s ThermoDox arguably the most well-known example [ 85 , 86 , 87 ]. There are several reports in the literature using internal and external stimuli to afford the release of nucleic acid cargos.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lipid nanoparticles (MLNs) systems are the third generation of lipid nanoparticles that have emerged as alternative to nanostructured lipid carriers to overcome some of their shortcomings [ 192 , 193 ]. MLNs, combining the advantages of double emulsions and solid lipid nanoparticles, allow the simultaneous encapsulation of hydrophilic and lipophilic compounds guarantying a combined therapy against many diseases [ 193 ].…”
Section: Antimicrobial Nanomedicine Drug Delivery Systemsmentioning
confidence: 99%
“…Multiple lipid nanoparticles (MLNs) systems are the third generation of lipid nanoparticles that have emerged as alternative to nanostructured lipid carriers to overcome some of their shortcomings [ 192 , 193 ]. MLNs, combining the advantages of double emulsions and solid lipid nanoparticles, allow the simultaneous encapsulation of hydrophilic and lipophilic compounds guarantying a combined therapy against many diseases [ 193 ]. The literature survey showed that Carvacrol (CAR, an antimicrobial natural phenolic monoterpene [ 194 , 195 , 196 , 197 , 198 ])-loaded nanoparticles have more attractive characteristics, such as good chemical stability, high solubility, low toxicity, controlled release rate as well as enhanced bioavailability [ 199 , 200 , 201 ].…”
Section: Antimicrobial Nanomedicine Drug Delivery Systemsmentioning
confidence: 99%
“…Regardless of this overabsorption, the majority of the supplemented vitamin B6 is excreted in urine as 4-pyridoxic acid (PA) [ 122 ]. Notably, high-performance athletes may benefit from vitamin B6 supplements as physical exercise increases the excretion of PA [ 123 ], with a study reporting lower B6 levels in endurance athletes after exercise [ 124 ]. Plasmatic PLP can increase 10-fold upon supplementation and respond within 1–2 weeks following depletion or repletion.…”
Section: Vitamin B6: Pyridoxinementioning
confidence: 99%